Characterization and impact of the sugarcane borer on sugarcane yield and quality - Rossato Jr., José A. de S. [UNESP]; Costa, Gustavo H. G. [UNESP]; Madaleno, Leonardo L.; Mutton, Márcia J. R. [UNESP]; Higley, Leon G.; Fernandes, Odair A. [UNESP] (Wiley, 2013)
The sugarcane borer, Diatraea saccharalis (F.) (Lepidoptera: Crambidae), is a key pest of sugarcane (Saccharum spp.). While damage caused by this pest has increased in the past 20 yr, studies investigating the insect-plant interactions are still lacking. Moreover, there is no information about the consequences of borer damage on the parameters of sugar quality. Therefore, two field experiments were performed during the 2010 and 2011 growing seasons in Brazil to compare the raw material and sugar quality of SP80-3280 sugarcane plants with and without the sugarcane borer. Plants were protected within screen cages and infested weekly during the 2010 and 2011 seasons, using egg masses starting at the second and third internode stage. At harvest, 25.77 and 19.01% of the internodes were bored by larvae (infestation intensity, II) in the first and second seasons, respectively. There was no correlation between the borer gallery total volume and II. The fiber content significantly increased with increasing II. The stalk biometric parameters, such as length, diameter, and yield, were not correlated with II. The sucrose yield significantly decreased with increasing II. Consequently, sugar yield losses were estimated at 8.83 and 19.80% per 1% bored internode for the first and second seasons, respectively. The concentration of phenolic compounds increased, and unclarified juice color quality decreased, with increasing II. Significant differences were detected in the quality of the sugar. These results should be confirmed for other sugarcane cultivars and incorporated into an economic injury level to enhance decision-making strategies for borer management. © 2013 by the American Society of Agronomy, 5585 Guilford Road, Madison, WI 53711. All rights reserved.